2020
DOI: 10.1111/ajt.15659
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and chemical dependency services at US transplant centers

Abstract: The purpose of this study was to assess the availability of mental health (MH) and chemical dependency (CD) services at US transplant centers, because appropriate psychosocial assessment and care is associated with better transplant outcomes. We used the 2017‐2018 American Hospital Association survey, Area Health Resource File, and Centers for Medicare & Medicaid Services Hospital Compare databases to quantify availability of services and examined associations of hospital‐ and health services area‐level charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In the real world, mental health services are typically provided as consultation services during the LT evaluation and the candidate selection process, and not during the waiting period in the follow-up period after LT. A recent survey of mental health and addiction services at nonfederal LT programs in the United States showed that while 94% of the programs offered mental health services, only 47% offered chemical dependency services and only 47% had access to their medical system. [105] Far fewer LT programs have addiction services colocated in an integrated clinic. However, for patients at risk for alcohol use recurrence, an inpatient program with detoxification may be necessary before being transitioned to an outpatient program.…”
Section: Aud Treatment In Patients With Ald: the Ground Realitymentioning
confidence: 99%
“…In the real world, mental health services are typically provided as consultation services during the LT evaluation and the candidate selection process, and not during the waiting period in the follow-up period after LT. A recent survey of mental health and addiction services at nonfederal LT programs in the United States showed that while 94% of the programs offered mental health services, only 47% offered chemical dependency services and only 47% had access to their medical system. [105] Far fewer LT programs have addiction services colocated in an integrated clinic. However, for patients at risk for alcohol use recurrence, an inpatient program with detoxification may be necessary before being transitioned to an outpatient program.…”
Section: Aud Treatment In Patients With Ald: the Ground Realitymentioning
confidence: 99%
“…Including social workers in HCT interventions may reduce barriers by providing improved linkages to health care and community-based services as well as greater psychosocial support leading to sustainable positive health outcomes (43). Prior studies have demonstrated that increased social work support services are associated with lower total hospital costs and increased probability of physician follow-up (44,45).…”
Section: Social Workersmentioning
confidence: 99%
“…Although some studies have shown that pretransplantation anxiety was not associated with graft failure or increased mortality [28], there are data to support that lifetime exposure to traumatic events increases morbidity and mortality risks in the transplant population [18,36]. PTSD is more common among transplant candidates and recipients than in the general population [37]. Overall, across all organ types, an estimated 12–18% of transplant recipients develop PTSD because of their transplant experience [38 ▪ ].…”
Section: Psychosocial Perspectivementioning
confidence: 99%